Development of an Android-Based Geographic Information System for Maneungteung Tourism Area in Cirebon Regency Using Location-Based Service (LBS) Method with Android Studio Version 2024.1.2 - Cahyawan, Afifudin Nur; Faizah, NM; Nurcahyo, Widyat (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Maneungteung Tourism Area in Cirebon Regency holds strong potential as a local attraction, yet the absence of an integrated information system limits visitor access to reliable tourism data. This study aims to develop an Android-based Geographic Information System (GIS) integrated with Location-Based Service (LBS) technology to enhance information accessibility, spatial accuracy, and management efficiency. The research employs the Agile Software Development approach using the Extreme Programming (XP) model, which emphasizes flexibility, iterative improvement, and continuous collaboration between developers and users. The system was built using Android Studio with Java as the main language, integrating Google Maps API for real-time spatial visualization and Firebase for database management and authentication. Functional and user acceptance testing demonstrated that the application runs reliably, displaying accurate destination information, navigation routes, and booking features. Administrators can manage data dynamically through a synchronized backend system. The integration of GIS and LBS technologies successfully improves tourism service delivery, promotes user engagement, and supports the digital transformation of tourism management in Cirebon Regency, particularly in the Maneungteung area.